PSYCHOANALYTIC DIMENSIONS OF IVAN FRANKO’S GREAT PROSE OF 1887–1893 - Svitlana M. Lutsak; Nataliia M. Vivcharyk (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2024)
In the article, elements of mythopoetics in Ivan Franko’s great prose of 1887–1893 are explored using the methodology of psychoanalysis. The writer’s projection of prototypes (in Jungian terms) anticipated the discoveries of psychoanalysts in the artistic text, and its precondition was Ivan Franko’s personal interest in the issue of the artist’s unconscious mental activity, as evidenced by his work “Secrets of Poetic Creativity”. The psychoanalytic vector of Franko’s works has been studied to a greater or lesser extent by scholars such as K. Dron, B. Tykholoz, Van Xiaoyui, T. Hundorova, N. Zborovska, R. Pikhmanets, and others. However, as of today, there is essentially no separate study of certain archetypal images and mythologems, like the Great Mother or the twin myth, in the artistic world of Ivan Franko, which is why the novelty and relevance of this article are justified. Despite the fact that the psychoanalytic and mythopoetic aspects of Ivan Franko’s prose have been thoroughly investigated, there remains an obvious interconnection of these aspects on the periphery of scholars’ interests, which, in our opinion, is worthwhile to consider as a poetological synthesis, constituting one of the most interesting characteristics of the writer’s artistic method. It is precisely in this that we see the novelty of the presented research. The purpose of the research is to study the psychoanalytic discourse in the great prose works of Ivan Franko from 1887 to 1993, including various aspects of the twin myth and the archetype of the Great Mother. The following tasks arise from the objective: To analyze the key vectors of the twin myth in the novel “Lel and Polel”; characterize the ambivalent manifestations of the Great Mother archetype in the image of the main heroine in the novel “For the Home Hearth”; identify transformations of Freudian ideas in the artistic structure of the novel “Foundations of Society”, considering their animistic component. The implementation of the set tasks necessitated the use of such methods as receptive-interpretative, psychoanalytic, mythopoetic, hermeneutic, and biographical. The study analyzes the psychoanalytic discourse in Ivan Franko’s great prose from 1887 to 1993, focusing on the diverse aspects of the twin myth and the archetype of the Great Mother. This takes into account the peculiarities of the development of early Ukrainian modernism with its characteristic mythologization of reality, stylistic experiments, and more. In the novel “Lel and Polel”, the dominant theme is the twin myth, through which the principle of the parity and duality of the world is realized. Love for one woman led to the decay, violating the maternal directive to “stick together”. The romantic rivalry between the twins over love for the same woman resulted in the violation of maternal directives, intense psychological experiences, and led to withdrawal from social activities and rejection of the role of enlightener. The novel “For the Home Hearth” is characterized by ambivalent manifestations of the archetype of the Great Mother. The image of the main heroine varies from the Lady of the Heart, Woman-Protectress, to the Terrifying Mother as the “instrument of temptation and vessel of sin”. Antos feels the influence of Anela’s animistic force, thus referring to his wife as “alternately an angel and a demon”. To enhance the sense of fear and the fatal ending, the author introduces the image of a widow carrying the imprint of “mortal anxiety”. The psychoanalytic discourse in Ivan Franko’s novel “Foundations of Society” correlates more with Freudian ideas. The article analyzes the imitation in the exposition of the person’s experiences during a psychoanalytic session with all its characteristic manifestations (“feeling of cold anxiety”, erotic dream, the effect of the film of dreams, a terrifying conversation with a man-“devil”, etc.), as well as hints at the son’s infantilism conditioned by the influence of the mother. It is noted that in the relationship between Olympia and Adas, the animistic component of the archetypal semantics of the Great Mother is manifested: a sense of powerlessness before the mother, admiration for her strong character, leading to a readiness to follow her instructions unquestionably. In his great prose, 1887–1893, the writer emerges as a true psychoanalyst, an expert on the unconscious factors of human mental activity. It seems that Ivan Franko, in modelling the inner world of his characters, to some extent, anticipates the discoveries of psychoanalysts in artistic texts. The modernist reevaluation of mythological and archetypal images, which often lose their integrity, embodying the disharmony between the world and the individual, attests to a new level of poetological synthesis, reflecting one of the most interesting features of the writer’s artistic method.